Enteric methane emission factor for dairy farming in Peru - Fernandez, Melisa (2024)
The objective of this study was to determine the enteric methane (CH4) emission factor (EF) at the national level for Peruvian dairy cattle following the IPCC Tier II (2006, 2019) methodology. Data were collected from seven regions of Peru and classified according to the type of feeding as intensive, semi-intensive or extensive. It included farm information (geolocation) and livestock information for two seasons of the year. At the national level, lactating cows obtained the highest EF with 117 kg CH4/head/year, followed by heifers from 15 to 24 months of age (91 kg), non-lactating cows (74 kg), heifers from 12 to 15 months of age (67 kg), calves (62 kg) and pre-weaned calves (16 kg). Additionally, the highest EF was reported for lactating cows in the intensive system (151.8 kg CH4/head), which is 46.8 kg CH4/head more per year than that reported in the semi-intensive and extensive systems in the same animal category. The combined uncertainty in all animal categories was low to very low (between 9.4 and 18.72%), except for that of lactating cows, which was low to medium (22.24 and 26.72%). These results allowed us to find the EF that exerts the most pressure according to the level of intensity in Peruvian dairy farming.